SURFACE AND INTRAMURAL REENTRANT PATTERNS DURING ATRIAL FIBRILLATION IN THE SHEEP - Berenfeld, Omer (Methods Inf Med, 2014)
BACKGROUND: Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia in humans and is predicted to dramatically increase its prevalence in the future. High-resolution mapping data and Fourier power spectral analysis with its dominant frequency support the hypothesis that AF in the structurally normal sheep heart and in some patients often presents organized drivers in the form of periodic surface re-entries or breakthroughs. Nevertheless, the dynamics of those surface patterns of activity, as well as their intramural components are still poorly understood. OBJECTIVE: to present data on AF waves from the surface of isolated sheep hearts and discuss the interpretation of their intramural patterns. METHODS: We used a combination of endocardial-epicardial optical mapping with phase and spectral analysis as well as computer simulation of the re-entrant activity in the myocardial wall RESULTS: Analysis of the surfaces’ optical mapping data in the phase domain reveals that activation of the posterior left atrium (PLA) consisted of alternating patterns of breakthroughs and reentries. The patterns on the endocardial and epicardial PLA surface at any given moment of time of the AF could be either identical or not identical, and the activity in the thickness of the PLA wall is hypothesized to conform to either ectopic discharge or reentrant scroll waves, but a definite evidence for the presence of such mechanisms is currently lacking. A universal minimal-principle theory is shown in a computer model to result in a tendency of the axis of the scroll waves to align with the myocardial fibers inside the wall. CONCLUSION: The tendency of filaments of scroll waves to align with myocardial fibers may contribute to the variety and intermittency of surface rotors seen in AF.